Peningkatan Kualitas Dan Kuantitas Sumberdaya Manusia Pada Kesatuan Pengelolaan Hutan Lindung (Kphl) Batutegi Dan Kota Agung Utara Di Provinsi Lampung - Siti Rohana; Christine Wulandari; Slamet Budi Yuwono (Jurnal Sylva Lestari, 2016)
Sustainable forest management aims to benefit maximum for the prosperity of the people. Achieving sustainable forest management, KPHL should pay attention to human resources (HR) managers. The purpose of the research was carried out in May-June 2014 is charting the quality and quantity of human resources in KPHL Batutegi and KPHL Kota agung Utara in the province of Lampung and drawing up recommendations for efforts to improve the quality and quantity of human resources needed by the KPHL. Data collected by direct observation in the field, interviews and analyzed quantitative and descriptive. Research results from the aspect of quality of human resources in KPHL Batutegi, of 39% has good quality and 61% of less quality as well as human resources in the KPHL Kota Agung Utara qualified 42% and less qualified 58%. The increase in the quantity human resources required 4 staff KPHL Batutegi general functional and 53 human resources functional position, while for KPHL Kota Agung Utara 16 staff of general functional human resources and 99 staff for certain functional position. Keywords: quantity, quality, human resources, KPHL